Pengaruh Green Hiring Terhadap Environmental Performances Dengan Green Performances Management And Compensation Sebagai Variabel Mediasi - Evi Silvana Muchsinati; Eriva Riesquita; Adineka Fatyandri (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – In the era of global awareness of sustainability, organizations are increasingly prioritizing environmentally friendly practices as part of their business strategies, including through green hiring. This approach aligns with the goals of the Sustainable Development Goals (SDGs), which emphasize environmental protection. However, research on the impact of green hiring on environmental performances, particularly in Indonesia's manufacturing sector, remains limited. Aim – This study aims to analyze the impact of green hiring on environmental performances in manufacturing companies in Batam and evaluate the mediating roles of green performance management and green compensation. Design/Methodology/Approach – The study employs a quantitative approach using Partial Least Squares Structural Equation co (PLS-SEM). The sample includes 279 respondents from PT. Panasonic Industrial Devices Batam and PT. Philips Industries Batam. Data were collected through an online questionnaire measuring green hiring, green performance management, green compensation, and environmental performances. Findings – The findings reveal that green hiring positively and significantly influences green performance management, green compensation, and environmental performances. Furthermore, green performance management and green compensation partially mediate the relationship between green hiring and environmental performances. These results align with previous studies, emphasizing the importance of integrating environmentally friendly practices into human resource management to enhance environmental performance. Conclusion – This study highlights that green hiring is a critical factor in improving environmental performance, both directly and through environmentally oriented performance management and compensation systems. Research Implications – The study contributes to the literature on green human resource management (GHRM) and offers practical insights for HR managers to enhance environmental performance through green recruitment and compensation policies. Research Limitations – The study is limited to the manufacturing sector in Batam and uses cross-sectional data, which may not be generalizable to other sectors or provide insights into long-term relationships between variables.